Gender dysphoria: Definitions, classifications, neurobiological profiles and clinical treatments - Giulio Perrotta (International Journal of Sexual and Reproductive Health Care - Peertechz Publications, 2020)
This work focuses on the theme of gender dysphoria and in particular on clinical, psychopathological and anatomy physiological elements, to understand if there are substantial elements to suppose the neurophysiological diversity between a dysphoric people and a not-dysphoric people, and therefore understand if these are the differences which cause the dysphoric condition or whether the dysphoric condition shapes the anatomy and physiology of the brain by inducing changes.